2012
DOI: 10.1080/00103624.2012.711876
|View full text |Cite
|
Sign up to set email alerts
|

Liming Decreases the Vertical Mobility of Potassium in Acidic Soils

Abstract: Liming increases soil negative charges and thus affects the chemical equilibrium of cations between the solid phase and the soil solution with consequences for the mobility of cations. The effects of lime and potassium chloride (KCl) addition on the vertical movement of potassium (K), calcium (Ca), and magnesium (Mg) were investigated in two Brazilian soils. The experiment was carried out in leaching columns. Treatments included a combination of rates of KCl (0, 50, 100, and 200 mg kg −1 K) and acidity levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
(23 reference statements)
0
6
0
2
Order By: Relevance
“…This explains the increase in K with greater depth following successive applications of LSM (Lourenzi et al, 2013;Grohskopf et al, 2016a;Oliveira et al, 2017). However, increases in negative charges in the soil induced by higher organic C content and pH values in the surface layer may also reduce K translocation to deeper soil layers (Ernani et al, 2012), as observed for the area fertilised for 15 years compared to the area fertilised for eight years ( Figure 4B and Table 2). Increases in soil K induced by LSM application agree with results reported by Oliveira et al (2017), which verified that K levels in pasture areas fertilised with LSM over 15 years were 2, 3 and even 4 times higher in the 0-10, 10-20 and 20-40 cm layers respectively, compared to those quantified in the native forest.…”
Section: Soil Nutrient Availabilitymentioning
confidence: 78%
“…This explains the increase in K with greater depth following successive applications of LSM (Lourenzi et al, 2013;Grohskopf et al, 2016a;Oliveira et al, 2017). However, increases in negative charges in the soil induced by higher organic C content and pH values in the surface layer may also reduce K translocation to deeper soil layers (Ernani et al, 2012), as observed for the area fertilised for 15 years compared to the area fertilised for eight years ( Figure 4B and Table 2). Increases in soil K induced by LSM application agree with results reported by Oliveira et al (2017), which verified that K levels in pasture areas fertilised with LSM over 15 years were 2, 3 and even 4 times higher in the 0-10, 10-20 and 20-40 cm layers respectively, compared to those quantified in the native forest.…”
Section: Soil Nutrient Availabilitymentioning
confidence: 78%
“…It may have happened because irrigations were annually carried out from November to January and it may have stimulated K ion displacement in the soil, mainly in soil presenting low CEC pH7.0 (4.7 cmol c kg -1 ). K displacement may also have happened in soil with history of limestone application, which increased Ca and Mg adsorption in functional groups of soil reactive particles and partly stimulated K displacement from the solid fraction to the solution (Werle et al, 2008;Ernani et al, 2012). Thus, it is necessary applying potassium fertilizer doses to the soil on a yearly basis, rather than just before vineyard implementation, in order to maintain K levels in the soil close to the original ones and in adequate amounts capable of meeting plant demands.…”
Section: Methodsmentioning
confidence: 99%
“…Available potassium was significantly higher in the treatment where calcium carbonate was applied as per lime requirement (S 2 L 3 ). In soils with pH dependent charges, increase in pH with liming enhances the CEC of soil thus improving the ability to retain potassium (Ernani et al, 2012).…”
Section: Available Potassiummentioning
confidence: 99%